A Novel Node Information Update Multicast Algorithm in Wireless Sensor Networks - Zhu Yonghua; Dong Zhiling; Pan ShunHong; Wang Lu; Zhang Qian; Wu Junjie (2009 International Conference on Networks Security, Wireless Communications and Trusted Computing, 2009)
Wireless sensor networks (WSN) are composed of a large number of sensor nodes which are connected by wireless channels. Some of these sensor nodes are regarded as critical nodes which are responsible for the management of the other nodes in their sphere. Therefore, update of node information must be implemented through these critical nodespsila multicast operation. In this paper, we present a novel node information update multicast (NIUM) algorithm to optimize the transmission performance among critical nodes. After applying with our algorithm, each critical node could explore a reasonable transportation way according to its distance apart from other critical nodes. Despite of the ideal assumption, our algorithm is also tested under different circumstances and the results prove that it behaves well for prompt node information update in wireless sensor networks. Both velocity and efficiency of the network can be improved tremendously.